2010
DOI: 10.1158/1538-7445.am10-2587
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 2587: In vitro plasma stability of human anti-CD70 antibody drug conjugate, MDX-1203

Abstract: MDX-1203 is a human anti-CD70 antibody conjugated to a pro-drug containing DNA alkylating cytotoxic Drug A. Drug A is composed of the anti-tumor compound Drug B, containing an ester linked protecting group, and a maleimide containing cleavable peptide linker designed to facilitate conjugation to the antibody. Mechanism of action of ADCs involve antibody mediated tumor specific delivery, cellular uptake, and intracellular pro-drug release and activation. Understanding the stability of the peptide linker as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Similar to irinotecan, MED-A appeared to be preferentially hydrolyzed by CES2 as well. The reported K m and k cat /K m of MED-A with CES2 were 1.1 μM and 900 s -1 M -1 , respectively, comparing with the respective 57 μM and 40 s -1 M -1 with CES1 [20,21]. In addition to the different substrate specificities, CES2 was found present in various tumor tissues [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to irinotecan, MED-A appeared to be preferentially hydrolyzed by CES2 as well. The reported K m and k cat /K m of MED-A with CES2 were 1.1 μM and 900 s -1 M -1 , respectively, comparing with the respective 57 μM and 40 s -1 M -1 with CES1 [20,21]. In addition to the different substrate specificities, CES2 was found present in various tumor tissues [31].…”
Section: Discussionmentioning
confidence: 99%
“…One of the key challenges in the preclinical development of α CD70_MED‐A was the species difference of plasma esterase activities. Previous studies suggested that the carboxylesterases was able to hydrolyze the carbamate protecting group when MED‐A was still conjugated with the antibody to yield α CD70_MED‐B (Figure B). The amide bond in the MED‐B portion of the ADC was subsequently hydrolyzed to yield an inactivated ADC ( α CD70_MED‐C) and two small molecule catabolites, Met‐A and ‐B, in the plasma circulation (Figure B).…”
Section: Introductionmentioning
confidence: 97%
“…A separate LBA reagent recognizing the activated ADC was required in order to adequately track both the precursor ADC and the activated ADC. Interestingly, the cleavage of this carbamate is reported to render the acyl indole payload susceptible to slow proteolytic cleavage resulting in loss of the warhead from the ADC [36,37].…”
Section: Carbamate and Ester Cleavage By Esterasesmentioning
confidence: 99%